Peningkatan Kemampuan Membaca Siswa Melalui Strategi Pembelajaran Kooperatif Tipe Make A Match dengan Menggunakan Media Kartu Bergambar pada Siswa Kelas VI di SDN Gendang Timur III - Maulana, Andre; Sama'; Agus Wahdian (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the reading ability of sixth-grade students at SDN Gendang Timur III, Gayam District, through the implementation of the cooperative learning strategy Make a Match using picture card media. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The instruments used included teacher and student observation sheets as well as reading comprehension tests. The results of the study showed an improvement in students’ reading skills. The average reading score increased from 62.2 in the pre-cycle to 68.8 in the first cycle and reached 74.8 in the second cycle. The mastery learning level also improved, rising from 40% in the pre-cycle to 60% in the first cycle, and 80% in the second cycle. This increase indicates that the Make a Match strategy supported by picture card media is effective in enhancing students’ reading comprehension and interest. Therefore, this strategy is recommended as an alternative for creating more active, enjoyable, and meaningful reading instruction in elementary schools.